1999
DOI: 10.1111/j.1600-0536.1999.tb06163.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin sensitization response of dialkyl (C6‐C13) phthalate esters

Abstract: Isolated case reports suggest that dermal contact with some phthalate esters may result in skin sensitization. This issue was investigated in guinea pig sensitization tests, but the results were inconclusive. Consequently, 7 dialkyl phthalate esters, (diisohexyl, diisoheptyl, di(2-ethylhexyl), diisononyl, diisodecyl, diundecyl and ditridecyl phthalates), ranging in carbon number from C6 to C13, were tested in a 104-person panel human repeated insult patch test (HRIPT) using the modified Draize procedure. Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…The fact that phthalate esters can facilitate the process of sensitization to FITC suggested that the co‐existence of different chemicals has some impact on the outcome of contact sensitization. In a human volunteer study in which phthalate esters with carbon numbers C6–C13 (including DEHP and DINP) were investigated by means of a patch test, negative results for skin sensitization were obtained [12]. However, in that study, phthalate esters with shorter alkyl chains were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that phthalate esters can facilitate the process of sensitization to FITC suggested that the co‐existence of different chemicals has some impact on the outcome of contact sensitization. In a human volunteer study in which phthalate esters with carbon numbers C6–C13 (including DEHP and DINP) were investigated by means of a patch test, negative results for skin sensitization were obtained [12]. However, in that study, phthalate esters with shorter alkyl chains were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…No reports exist of dermal or inhalation toxicity of DEHP in adult humans, and DEHP is neither a dermal irritant nor a sensitizer (ATSDR 2002; Medeiros et al 1999). DEHP does not appear to be readily absorbed through human skin (ATSDR 2002).…”
mentioning
confidence: 99%
“…Phthalates are also employed in skin care products or other products as stabilizers, binders, emulsifiers, and lubricants, including skin moisturizers, mosquito repellents, perfumes, deodorants, shampoos, and nail polishers [23]. There are many reports of allergic contact dermatitis (ACD) [24,25], and phthalates were even responsible for recent increase prevalence of irritant contact dermatitis (ICD) [26]. Prenatal exposure to BBzP, as measured by levels of MBzP in spot urine samples during the third trimester of pregnancy, has been associated with a risk of developing eczema in early childhood [27].…”
Section: The Toxic Effects Of Edcs On the Skinmentioning
confidence: 99%